European labour market policies in (the) crisis - Clasen, Jochen; Clegg, Daniel; Kvist, Jon (Brussels, 2012)
" This working paper by Jochen Clasen and Daniel Clegg, of the University of Edinburgh, together with Jon Kvist of the University of Southern Denmark, examines the nature of impact of the economic and political challenges engendered by the “Great Recession” on labour market policy reforms in Europe. The authors thus consider the question of whether the economic crisis has also brought a labour market policy reform crisis in its wake.